ENHANCED DIESEL PRODUCTION VIA MODELLING AND SIMULATION OF CRUDE DISTILLATION UNIT II OF KADUNA REFINING AND PETROCHEMICAL COMPANY (FUDMA JOURNAL OF SCIENCES, 2020)
Human activities in the world has increased due to the growing population of people and commercial activities which results in the demand growth for diesel heavy trucks in the delivery of goods. This study was carried out to investigate suitable operating conditions that would yield higher diesel production and minimum residue using the crude distillation unit II of Kaduna Refining and Petrochemical Company (KRPC) as a case study. The virtual representation of the process was modelled successfully using design procedures and operational data of crude distillation unit of KRPC while the Aspen Hysys 2006 process simulator was used to simulate the unit using Venezuelan crude oil as the feedstock. A rigorous analysis was made on operating conditions such as the temperature and diesel steam mass rate that led to the optimization of the unit based on some key parameters. After successfully simulating the crude distillation unit of KRPC, the optimum feed temperature was found to be 290 Â°C and the diesel obtained was 94360.34 kg/hr as compared to 313.2 Â°C and 80678.10 kg/hr normally obtained at the KRPC. This showed about 13.2 % increase in diesel yield
Keywords: Aspen Hysys, CDU, Optimization